Quarreling Siblings or Friendly Neighbours? Turbulent Nature of Indo-Pakistan Relationship since 1947 - Chakrabarti, Shantanu (UNISCI Discussion Papers, 2012)
The process of decolonization and partition in South Asia led to internal discrepancies and evolution of regional dynamics often competitive and conflict-prone in nature. This has been particularly true in case of evolving bilateralism between India and Pakistan since 1947. While intermittent conflicts along with continuous tension and rivalry have been main features of the bilateral relationship, it has not been a case of unrelenting hostility on both sides. There have been ‘bright spots’ of engagement connecting the two countries at various official and non-official levels of engagement. Betterment of ties has become particularly essential as regional dynamics has eased to be a ‘zero-sum’ game for either country in the post Cold period as a ‘failed’ or ‘radicalized and ‘balkanized’ Pakistan would not only jeopardize any prospects of peace and stability in South Asia but would also become a terrible global problem.
Keywords: South Asia; India; Pakistan; Ethnicity; Nationalism; Partition; Rivalry; Cooperation; Conflict.